2016
DOI: 10.4110/in.2016.16.3.189
|View full text |Cite
|
Sign up to set email alerts
|

Differential Chemokine Signature between Human Preadipocytes and Adipocytes

Abstract: Obesity is characterized as an accumulation of adipose tissue mass represented by chronic, low-grade inflammation. Obesity-derived inflammation involves chemokines as important regulators contributing to the pathophysiology of obesity-related diseases such as cardiovascular disease, diabetes and some cancers. The obesity-driven chemokine network is poorly understood. Here, we identified the profiles of chemokine signature between human preadipocytes and adipocytes, using PCR arrays and qRT-PCR. Both preadipocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 23 publications
0
25
0
1
Order By: Relevance
“…To determine whether allogenic MSCs actively attracted T cells, we first assessed the expression profiles of chemokines and chemokine receptors that are likely to mediate T cell migration2728. We found that MSCs expressed mRNAs for CCL2, CCL3, CCL4, CXCL10, and CXCL12, and CCL2 and CXCL12 proteins were detectable by ELISA in conditioned supernatants (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To determine whether allogenic MSCs actively attracted T cells, we first assessed the expression profiles of chemokines and chemokine receptors that are likely to mediate T cell migration2728. We found that MSCs expressed mRNAs for CCL2, CCL3, CCL4, CXCL10, and CXCL12, and CCL2 and CXCL12 proteins were detectable by ELISA in conditioned supernatants (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CCL18 is associated with some human cancer types including ovarian cancer 31 , 32 . CCL23 plays a role in subclinical systemic inflammation and associated with atherogenesis 33 . CCL8 is strengthened in stromal fibroblasts at the tumor border and in tissues at which breast cancer cells incline to metastasize such as the lungs and the brain 34 , 35 .…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, treatment with the lipid-lowering agent atorvastatin in a randomized controlled trial reduced circulating levels of eotaxin and mRNA expression of its chemokine receptor CCR5 in peripheral CD14(+) monocytes (28). Levels of MCP1 and eotaxin were also found to be predominantly expressed in pre-adipocytes compared with adipocytes, suggesting a role of these chemokines in adipogenesis (29). In our study, there was a positive correlation between the circulating levels of MCP1 and eotaxin; however, while no change in circulating levels of eotaxin was observed in children with obesity, a significant decrease in eotaxin levels was found in the IR patients.…”
Section: Discussionmentioning
confidence: 99%